Avaliação do potencial patogênico in vitro e in vivo de linhagens de Pseudogymnoascus spp., Aspergillus thermomutatus e Rhodotorula mucilaginosa presentes em ecossistemas da Antártica - Eldon Carlos Queres Gomes (2022)
Considered an extreme environment, Antarctica has borderline survival characteristics for most living beings, but some microorganisms, among which fungi stand out, are able to colonize and occupy its different ecosystems. Given the diversity of the fungal community currently known, only a small part is reported to be pathogenic for humans. However, some studies have shown that in the different extreme ecosystems of Antarctica, genera and species known to be pathogenic for humans and animals have been reported, which have demonstrated pathogenicity in in vitro assays. Among these fungi are those of the genera Pseudogymnoascus, Aspergillus and Rhodotorula. The genus Pseudogymnoascus harbors among its species Pseudogymnoascus destructans, which is psychrophilic, pathogenic and responsible for reducing the population of bats through White-Nose Syndrome in the United States, Europe and Palearctic Asia. Many reported Pseudogymnoascus antarctic lineages have shown high genetic similarity to P. destructans. The genus Aspergillus is ubiquitous and often found in the most varied substrates in Antarctica, it has characteristics that help its survival in extreme conditions. Rhodotorula mucilaginosa is also found in Antarctica, which has been considered an opportunistic pathogen emerging from humans and animals. Considering some factors such as: (i) the occurrence of these opportunistic fungi of humans and animals in Antarctic ecosystems, which under normal conditions would be trapped in their different substrates/habitats that they colonize due to cold/freezing and (ii) the effect of climate change in the region, especially the gradual increase in temperature in recent decades, attention is drawn to the possibility of these substrates being able to thaw and release such species with pathogenic potential out of Antarctica. Thus, this thesis aimed to evaluate the pathogenic potential of strains of Pseudogymnoascus spp., and of the species Aspergillus thermomutatus and R. mucilaginosa obtained from soil, lichen stalks and permafrost from Antarctica through in vitro and in vivo experiments. For this, nine in vitro virulence factor tests were performed to determine the pathogenicity of Antarctic fungi. Of the 11 isolates of Pseudogymnoascus spp. tested, Pseudogymnoascus sp. UFMG 8532 showed hemolytic activity, growth at different pH, production of hydrolytic enzymes (phospholipase and esterase) and spores capable of penetrating pulmonary alveoli. Aspergillus thermomutatus UFMGCB 17415 showed hemolytic activity, growth at different pH, growth at 45 °C and production of hydrolytic enzymes (phospholipase and proteinase) and R. mucilaginosa UFMGCB 17448 and 17473 hemolytic activity, growth at different pH, growth at 50 °C and production of hydrolytic enzymes (esterase and phospholipase). Due to the broad spectrum of in vitro activities, Pseudogymnoascus sp. UFMG 8532, A. thermomutatus UFMGCB 17415 and R. mucilaginosa UFMGCB 17448 and 17473 were submitted to in vivo pathogenicity tests using Tenebrio molitor models and BALB/c mice. The isolate Pseudogymnoascus sp. UFMGCB 8532 killed 100% of T. molitor larvae in 1 day; A. thermomutatus UFMGCB 17415 caused the death of all larvae in six days, R. mucilaginosa UFMGCB 17473 showed lethality of approximately 75% on the first day, evolving to 100% on the third day. The isolate R. mucilaginosa UFMGCB 17448 showed lethality close to 40% on the first day, evolving to 100% at the end of three days. In the model using BALB/c mice, survival, behavior and recovery of the fungal load inoculated in the animals were evaluated. For all tested isolates, it was found the possibility of causing disease in mice, causing fluctuations in weight, motor behavior, function and sensory reflex and finally changes in the psychiatric status of all animals. Thus, Pseudogymnoascus sp. UFMGCB 8532, A. thermomutatus UFMGCB 17415 and R. mucilaginosa UFMGCB 17448 and 17473 studied in this work and obtained from substrates/habitats that suffer major impacts from climate change in the region, indicates that Antarctica may harbor species/lineages with different virulence factors and pathogenicity to animals and humans, in particular those with some degree of immunosuppression. The results obtained in this study warn that climate change in Antarctica (mainly the increase in temperature) can release fungi and other pathogenic microorganisms of humans and animals, which are geographically isolated and trapped in their substrates/habitats characteristic of Antarctica (such as the stems of endemic lichens, unique soils and permafrost from which the target fungi of this study were obtained), which can be transported from Antarctica to different locations around the globe through biological and non-biological vectors. Therefore, further studies of the Antarctic microbiota and assessment of its pathogenic potential are of fundamental importance for monitoring and controlling emerging pathogenic microorganisms from extreme natural ecosystems.